Systematics and biogeography of Hemidactylus homoeolepis Blanford, 1881 (Squamata: Gekkonidae), with the description of a new species from Arabia - Vasconcelos, Raquel; Carranza, Salvador (Zootaxa, 2014)
A new species of gecko of the genus Hemidactylus (Squamata: Gekkonidae) is described from Oman and extreme eastern Yemen. Hemidactylus minutus sp. nov. is characterized morphologically by its very small size, being the smallest Hemidactylus in mainland Arabia, absence of enlarged tubercles anywhere on the body, expanded subcaudal scales beginning some way from tail base, number of preanal pores, number of lamellae under the first and fourth toes, and weakly contrasted black and white banded pattern on the ventral part of tail. It is also genetically distinct from H. homoeolepis to which it has previously been referred, and from all other closely related Hemidactylus from the arid clade in DNA sequence data for mitochondrial (12S, cyt b, ND4) and three nuclear (RAG1, MC1R, c‑mos) markers. An adult female from southern Yemen and a badly preserved juvenile from southwestern Saudi Arabia previously assigned to H. homoeolepis are morphologically differentiated from this species and from H. minutus sp. nov. and temporarily referred to as Hemidactylus sp. 12 and Hemidactylus sp. 13, respectively until more specimens are collected and analyzed. Up to now, H. homoeolepis was the only non-endemic native species of the Socotra Archipelago. With the description of H. minutus sp. nov., all native reptile species of Socotra are now endemic, such that this archipelago has one with the highest number of endemic reptiles in relation to its small size. In addition, as a result of our taxonomic change, the area of occupancy and extent of occurrence of H. homoeolepis have changed dramatically and thus its conservation status should be updated. Although H. minutus sp. nov. seems widely distributed and relatively abundant, its conservation status should also be re-evaluated.